(untitled) (Scientific journal of the Fergana State University, 2023)
This article deals with the Russian empire in 1897–1920 and later the Soviet government’s colonial nature of the Turkestan census, which took place in on the instructions of representatives. In addition, the article explains the objectives which were set by the Russian Empire and the Soviet government on the basis of the various primary sources’ comparison. This article includes the preliminary planning of the country’s economy based on the final results of the activities carried out over the years and the distribution of future work to the regions (mainly the local population) based on the final statistical figures collected at the end of these activities. The article also provides a number of scientific conclusions for some shortcomings of the census in the country